Intellectual Capital Di Indonesia: Tinjauan Literatur - Zul Azmi; Rara Baitul Yuli Aprian; Dian Putri Riri Arinji; Afnelya Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to map the direction and research trends of Intellectual Capital (IC) studies in Indonesia using a Systematic Literature Review (SLR) approach. A total of 20 articles from SINTA 1 and 2 accredited accounting journals published between 2020 and 2024 were analyzed based on key topics, research methods, research subjects, and publication quality. The results reveal that most studies employ a quantitative approach using the VAIC™ model and regression or panel data methods, focusing mainly on the banking and manufacturing sectors. The five dominant themes include the impact of IC on financial performance, VAIC™ efficiency, IC disclosure, IC components (HC, SC, RC), and industry-specific contexts. There is a notable lack of qualitative research and exploration of non-financial sectors. These findings highlight the need for more diverse methodological approaches and standardized IC disclosure in Indonesia to enhance academic contributions and business relevance.